The fifth quarter. 1 - Dawson, Mike, 1975- (First Second, 2021)
Fourth-grader Lori Block doesn't care that she has to play in the "fifth quarter," a special period before her fourth-grade travel basketball team's real games begin so that the not-so-good players can practice in games against each other--she is just happy to have the chance to hone her skills. Lori pursues her passion, seeks confidence at school and at home, and hopes to one day play in the real travel basketball games.